1990
DOI: 10.1093/geronj/45.4.p116
|View full text |Cite
|
Sign up to set email alerts
|

Next Steps in Describing Aging and Disease in Longitudinal Studies

Abstract: Longitudinal studies have contributed much to the understanding of aging. Traditionally, age-specific changes in physiological functioning are inferred from studies in which persons with disease processes believed to be relevant to the function in question are excluded from the results. The main theme of this review is that, in the future, studies of aging must better attempt to capture the interplay between disease and aging processes. A variety of research results, mostly from the Baltimore Longitudinal Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…Due to a lack of availability of longitudinal data as well as non-established criterion to identify significant biomarkers of aging, there is little consensus among researchers concerning BA estimation in humans. Recently, longitudinal human aging studies have reported that age-related change is not uniform (Ekonomov et al, 1989;Fozard et al, 1990). There is no clear pattern across all physiological systems.…”
Section: Biomarkers Of Aging In Women and The Rate Of Longitudinal Chmentioning
confidence: 99%
“…Due to a lack of availability of longitudinal data as well as non-established criterion to identify significant biomarkers of aging, there is little consensus among researchers concerning BA estimation in humans. Recently, longitudinal human aging studies have reported that age-related change is not uniform (Ekonomov et al, 1989;Fozard et al, 1990). There is no clear pattern across all physiological systems.…”
Section: Biomarkers Of Aging In Women and The Rate Of Longitudinal Chmentioning
confidence: 99%
“…The number of medical diagnoses and medications used tend to increase sharply after 60 years of age [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…As with vision, age-related changes in auditory thresholds occur neurally as well as at the level of the end organ [5]. It has been suggested that both sensory and cognitive aging are due to the same brain-related changes [3].…”
Section: Introductionmentioning
confidence: 99%